Microsatellite Instability in Patients With Stage III Colon Cancer Receiving Fluoropyrimidine With or Without Oxaliplatin: An ACCENT Pooled Analysis of 12 Adjuvant Trials. Issue 6 (20th February 2021) - Cohen, Romain; Taieb, Julien; Fiskum, Jack; Yothers, Greg; Goldberg, Richard; Yoshino, Takayuki; Alberts, Steven; Allegra, Carmen; de Gramont, Aimery; Seitz, Jean-Francois; O'Connell, Michael; Haller, Daniel; et al.
Abstract : PURPOSE: In patients with stage III colon cancer (CC) whose tumors demonstrate microsatellite instability (MSI), the efficacy of adjuvant fluoropyrimidine (FP) with or without oxaliplatin has not been clearly demonstrated and the prognostic value of MSI remains uncertain. MATERIALS AND METHODS: Individual patient data from the ACCENT database were used to evaluate the effect of FP with or without oxaliplatin on disease-free survival (DFS) and overall survival (OS) among patients with MSI stage III CC and the prognostic value of MSI in patients treated with FP plus oxaliplatin, by stratified Cox models adjusted for demographic and clinicopathological factors. RESULTS: MSI status was available for 5, 457 patients (609 MSI, 11.2%; 4848 microsatellite stable [MSS], 88.8%) from 12 randomized clinical trials (RCTs). Oxaliplatin significantly improved OS of MSI patients from the two RCTs testing FP with or without oxaliplatin (n = 185; adjusted hazard ratio [aHR] = 0.52, 95% CI, 0.28 to 0.93). Among the 4, 250 patients treated with FP plus oxaliplatin (461 MSI and 3789 MSS), MSI was associated with better OS in the N1 group compared with MSS (aHR = 0.66; 95% CI, 0.46 to 0.95) but similar survival in the N2 population (aHR = 1.13; 95% CI, 0.86 to 1.48; P interaction = .029). The main independent prognosticators of MSI patients treated with FP plus oxaliplatin were T stage (aHR = 2.09; 95% CI, 1.29 to 3.38) and N stage (aHR = 3.57; 95% CI, 2.32 to 5.48). Similar results were observed for DFS in all analyses. CONCLUSION: Adding oxaliplatin to FP improves OS and DFS in patients with MSI stage III CC. Compared with MSS, MSI patients experienced better outcomes in the N1 group but similar survival in the N2 group.